2018
DOI: 10.1002/bmc.4446
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the chemical constituents in Hongjingtian injection by liquid chromatography quadrupole time‐of‐flight mass spectrometry

Abstract: Hongjingtian injection is made from Rhodiola wallichiana and used in the treatment of stable angina pectoris associated with coronary heart disease. In this study, the chemical constituents in Hongjingtian injection were comprehensively studied using liquid chromatography quadrupole time-of-flight mass spectrometry. A total of 49 compounds were identified or assumed, including 10 organic acids, nine phenylethanoids, 10 phenylpropanoids, two flavonoid glycosides, seven monoterpene glycosides, seven octylglycosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The characteristic fragments were [M–H–C 2 H 4 ] - ( m/z 169.0138) and [M–H–C 2 H 4 –CO 2 ] - ( m/z 125.0239). Comparison with literature data [ 25 ] and library alignment ( Fig. S4B ; score: 94) revealed that compound 31 was ethyl gallate, a component of Rhodiolae Crenulatae Radix Et Rhizoma .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The characteristic fragments were [M–H–C 2 H 4 ] - ( m/z 169.0138) and [M–H–C 2 H 4 –CO 2 ] - ( m/z 125.0239). Comparison with literature data [ 25 ] and library alignment ( Fig. S4B ; score: 94) revealed that compound 31 was ethyl gallate, a component of Rhodiolae Crenulatae Radix Et Rhizoma .…”
Section: Resultsmentioning
confidence: 91%
“…In total, 104 compounds, including alkaloids, flavonoids, phenols, phenolic acids, phenylpropanoids, quinones, terpenoids, and other phytochemicals, were putatively identified (as listed in Table 1 [ [16] , [17] , [18] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] ]) using the library alignment method. According to previous studies [ [16] , [17] , [18] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] ], the identified compounds are present in the herbs used in the LHQW formulation. No phytochemical was identified from Dryopteridis Crassirhizomatis Rhizoma .…”
Section: Resultsmentioning
confidence: 99%
“…R. crenulata is the official species listed in the Chinese Pharmacopoeia (version of 2020), while some other species are also commonly used, such as R. wallichiana, R. angusta, and R. sachalinensis [65,66]. Specifically, R. wallichiana is the only species that has been developed to injection for treating stable angina pectoris associated with coronary heart disease [67]. In light of the diverse functions of Rhodiola, more and more products have been developed.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, R . wallichiana is the only species that has been developed to injection for treating stable angina pectoris associated with coronary heart disease [ 67 ]. In light of the diverse functions of Rhodiola , more and more products have been developed.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical constituents of RWC injection (RWCI) have been comprehensively studied. On the one hand, a total of 49 compounds including 10 organic acids, 9 phenylethanoids, 10 phenylpropanoids, 2 flavonoid glycosides, 7 monoterpene glycosides, 7 octylglycosides, and 4 other types of compounds were identified using the ultrahigh-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-Q/TOF-MS) analysis method [14]. On the other hand, the fingerprint RWCI had been established by HPLC [15].…”
Section: Introductionmentioning
confidence: 99%